Kruskal-Wallis Analysis in Determining Differences in Mathematical Problem-Solving Ability Based on Level of Learning Interest - Shecha Salsabila; Akmal Tsaqifiya Salma; Sintha Sih Dewanti; Qotrunnada Qotrunnada; Waffiq Lanaa Zakya A'maali (Media Pendidikan Matematika, 2025)
Mathematics demands high-level thinking skills, especially in problem-solving, and is characterized by systematic and logical reasoning. Beyond cognitive aspects, affective factors such as students’ interest in learning also influence their engagement and success. This study investigates differences in algebraic problem-solving ability based on students' interest levels and explores the relationship between the two variables. A comparative quantitative approach was used with Kruskal-Wallis non-parametric analysis and a correlation test. The sample consisted of 30 seventh-grade students at an MTs in Yogyakarta, grouped into low, medium, and high interest categories. Data were collected through a learning interest questionnaire and an algebra problem-solving test. The Kruskal-Wallis results showed a significance value of 0.135 (>0.05), indicating no significant difference in problem-solving ability among the groups. Similarly, the correlation test revealed no significant relationship between interest and ability. These findings suggest that learning interest does not directly affect students' algebraic problem-solving skills. Future research could explore other factors influencing mathematical problem-solving performance.